2023
DOI: 10.2196/38125
|View full text |Cite
|
Sign up to set email alerts
|

How Natural Language Processing Can Aid With Pulmonary Oncology Tumor Node Metastasis Staging From Free-Text Radiology Reports: Algorithm Development and Validation

Abstract: Background Natural language processing (NLP) is thought to be a promising solution to extract and store concepts from free text in a structured manner for data mining purposes. This is also true for radiology reports, which still consist mostly of free text. Accurate and complete reports are very important for clinical decision support, for instance, in oncological staging. As such, NLP can be a tool to structure the content of the radiology report, thereby increasing the report’s value. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…Following previous researches [4][5][6], we calculated the accuracy score, or the proportion of correct answers, for the T, N, and M categories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following previous researches [4][5][6], we calculated the accuracy score, or the proportion of correct answers, for the T, N, and M categories.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 summarizes previously suggested methods for automating lung cancer staging from radiology reports. Rule-based methods achieved an accuracy score of around 0.9 for the T and N categories [4][5][6],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in nuclear medicine, several studies have been published on NLP and oncologic imaging, such as finding bone metastasis in free-text bone scintigraphy reports [ 10 ]. Efforts to explore the potential of NLP in this field are illustrated by research published on finding pulmonary nodules and its characteristics in radiological reports [ 11 ] and finding a Lung-RADS classification out of structured reports used in pulmonary CT screening [ 12 ], as well as identifying staging characteristics about lung carcinoma in free-text radiology reports [ 13 15 ]. NLP is able to extract the TN stage of pulmonary oncology from the free-text radiological report of diagnostic staging CT scans by analyzing the text for this specific information and was shown by a rule-based TN-CT algorithm [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to explore the potential of NLP in this field are illustrated by research published on finding pulmonary nodules and its characteristics in radiological reports [ 11 ] and finding a Lung-RADS classification out of structured reports used in pulmonary CT screening [ 12 ], as well as identifying staging characteristics about lung carcinoma in free-text radiology reports [ 13 15 ]. NLP is able to extract the TN stage of pulmonary oncology from the free-text radiological report of diagnostic staging CT scans by analyzing the text for this specific information and was shown by a rule-based TN-CT algorithm [ 13 15 ]. This research showed that it is possible to automatically extract T and N stage from free-text radiological reports with accuracy scores of 0.84–0.85.…”
Section: Introductionmentioning
confidence: 99%